2023
DOI: 10.1371/journal.pntd.0011060
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ABO and RhD blood types on Babesia microti infection

Abstract: Background Babesiosis is an emerging infectious disease caused by intraerythrocytic Babesia parasites that can cause severe disease and death. While blood type is known to affect the mortality of Plasmodium falciparum malaria patients, associations between red blood cell (RBC) antigens and Babesia microti infection and disease severity are lacking. Methods We evaluated RhD and ABO blood types of Babesia-infected (18S rRNA reactive) blood donors in 10 endemic states in the Northeastern and northern Midwestern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Our results also suggest that any possible differences in the intrinsic nutrients between the ABO blood groups do not have any effects on the multiplication rate of the parasite. This study is in agreement with a recent clinical study on blood donors and patients admitted with B. microti infections, in which they could not find any association between ABO blood groups and risk of getting infected, having high peak parasitemias or intensive care unit admissions [ 17 ]. However, this same study found RhD+ individuals to be less susceptible to Babesia infection than RhD- individuals.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results also suggest that any possible differences in the intrinsic nutrients between the ABO blood groups do not have any effects on the multiplication rate of the parasite. This study is in agreement with a recent clinical study on blood donors and patients admitted with B. microti infections, in which they could not find any association between ABO blood groups and risk of getting infected, having high peak parasitemias or intensive care unit admissions [ 17 ]. However, this same study found RhD+ individuals to be less susceptible to Babesia infection than RhD- individuals.…”
Section: Discussionsupporting
confidence: 93%
“…Whilst we investigated here for the first time the influence of ABO on Babesia invasion and multiplication parameters, there are numerous other blood group systems that are independently inherited but not routinely typed. Some of them have been implicated in other host–pathogen interactions, either as receptors or other susceptibility or resistance factors [ 17 , 39 , 40 ] and may constitute future targets of study. Documentation of the blood groups of babesiosis patients and any associated unique or severe reactions across different regions will also help to enhance our knowledge about the interactions of this important parasite with humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation